<span>12 * 1/6 * 1 1/2 *3 3/4 *4 1/5 = </span><span>47 1/4
</span><span><span>12 * 1/6 = 2</span>
2*1 1/2 = 2* 3/2 = 3
3* 3 3/4 = 3*15/4=45/4
45/4*4 1/5 = 45/4*21/5=189/4 = 47 1/4
3 * 5 1/4 * 1 1/7*5 1/2 *4/11</span>= 36
<span>3 * 5 1/4 = 3*21/4=63/4
63/4*1 1/7 = 63/4*8/7=18
18*5 1/2= 18*11/2=99
99*4/11=36
</span>
Вот так получилось у меня
Ответ:
х= -1 и у=3
Пошаговое объяснение:
х+у-2=0
1) х=-1 и у=3
-1+3-2=0
2)х= -8 и у=6
-8+6-2= -4
Вывод: первая пара является решением уравнения
3.4у+0.65=0.9у-25.6
3.4у-0.9у=-25.6-0.65
2.5у=-26,25
у=-26,25:2,5
у=-10,5